Tick-Borne Encephalitis Virus Structural Proteins Are the Primary Viral Determinants of Non-Viraemic Transmission between Ticks whereas Non-Structural Proteins Affect Cytotoxicity. - Maxim A Khasnatinov; Andrew Tuplin; Dmitri J Gritsun; Mirko Slovak; Maria Kazimirova; Martina Lickova; Sabina Havlikova; Boris Klempa; Milan Labuda; Ernest A Gould; Tamara S Gritsun (PLoS ONE)
Over 50 million humans live in areas of potential exposure to tick-borne encephalitis virus (TBEV). The disease exhibits an estimated 16,000 cases recorded annually over 30 European and Asian countries. Conventionally, TBEV transmission to Ixodes spp. ticks occurs whilst feeding on viraemic animals. However, an alternative mechanism of non-viraemic transmission (NVT) between infected and uninfected ticks co-feeding on the same transmission-competent host, has also been demonstrated. Here, using laboratory-bred I. ricinus ticks, we demonstrate low and high efficiency NVT for TBEV strains Vasilchenko (Vs) and Hypr, respectively. These virus strains share high sequence similarity but are classified as two TBEV subtypes. The Vs strain is a Siberian subtype, naturally associated with I. persulcatus ticks whilst the Hypr strain is a European subtype, transmitted by I. ricinus ticks. In mammalian cell culture (porcine kidney cell line PS), Vs and Hypr induce low and high cytopathic effects (cpe), respectively. Using reverse genetics, we engineered a range of viable Vs/Hypr chimaeric strains, with substituted genes. No significant differences in replication rate were detected between wild-type and chimaeric viruses in cell culture. However, the chimaeric strain Vs[Hypr str] (Hypr structural and Vs non-structural genomic regions) demonstrated high efficiency NVT in I. ricinus whereas the counterpart Hypr[Vs str] was not transmitted by NVT, indicating that the virion structural proteins largely determine TBEV NVT transmission efficiency between ticks. In contrast, in cell culture, the extent of cpe was largely determined by the non-structural region of the TBEV genome. Chimaeras with Hypr non-structural genes were more cytotoxic for PS cells when compared with Vs genome-based chimaeras.